Immunogenetic Markers Definition in Latvian Patients with Lyme Borreliosis and Lyme Neuroborreliosis - Kovalchuka, Lilija (Int J Environ Res Public Health, 2016)
The aim of this study was to determine the human leukocyte antigen (HLA)-DRB1 alleles in two groups of patients in Latvia: patients with Lyme borreliosis and patients with Lyme neuroborreliosis. The study included 216 patients with Lyme borreliosis, 29 patients with Lyme neuroborreliosis and 282 control persons. All surveyed persons were residents of Latvia. The HLA-DR genotyping was performed by polymerase chain reaction- sequence specific primer (PCR-SSP). The predisposition to the Lyme borreliosis is associated with the HLA-DRB1*07, -DRB1*17(03), -DRB1*04, -DRB1*15(02) alleles. The allele -DRB1*11(05), -DRB1*14(06) and -DRB1*13(06) were significantly more frequent in controls. In-group with Lyme neuroborreliosis differences were found for the -DRB1*07 and -DRB1*04 alleles, but only HLA-DRB1*07 allele was statistically significant after Bonferroni correction and associated with Lyme neuroborreliosis in Latvian patients.